Healing or stealing? : medical charlatans in the new age - Abgrall, Jean-Marie (Algora Pub., 2000)
Abgrall is one of the world's top experts on cults and the pseudo health movements that prey upon people in need. A practicing psychiatrist and criminologist, he says "so-called alternative medicine sometimes crosses the line and becomes pure crookery." A